PENGARUH INDEPENDENSI, KOMPETENSI, PROFESIONALISME DAN INTEGRITAS TERHADAP KUALITAS AUDIT (Studi Kasus pada Kantor Akuntan Publik yang berada di Kota Semarang) - Anis Aghniyaul Haqque, 15.05.52.0322; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2019)
Public Accountants must improve the quality of the audit they produce. Audit quality is determined by independence, competence, professionalism and integrity. Therefore the purpose of this study is to test the independence, competence, professionalism and integrity of audit quality. The population in this study is the auditor who works at the Public Accounting Firm in Semarang and has at least 3 years experience as an auditor. Sampling was 44 respondents. The primary data collection method used is the questionnaire method. Data is analyzed using multiple linear regression models. The results of the study show that the competition proves to be significantly positive towards audit quality. Whereas independence, professionalism and positive integrity have no significant effect on audit quality.